FIELD EVALUATION OF SOME CHEMICAL PESTICIDES IN CONTROLLING THE GREEN PEACH APHID (MYZUS PERSICAE SULZER) (HEMIPTERA: APHIDIDAE) ON EGGPLANT CROP IN AL-‘ALAM DISTRICT (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This study investigates the efficacy of various pesticides on the control of aphid nymphs and adults, specifically focusing on the species M. persica. Results indicated that the Closer pesticide produced the most significant reductions in nymph populations, achieving average counts of 6.31 and 5.98 nymphs/in² after one and three days, respectively, with corresponding mortality rates of 47.81% and 48.7%. In contrast, the Pento pesticide exhibited higher nymph counts, while the plant extract Azadirachtin demonstrated effective control over a longer period, achieving a mortality rate of 63.42% after 21 days. The adult aphid population also responded significantly to treatment, with Closer showing the lowest counts (0.8 to 0.07 aphids/in²) across all time points, demonstrating substantial effectiveness compared to water and Acetamprid treatments. The findings underscore the complexities of aphid control, indicating that while chemical pesticides can provide immediate results, their efficacy may diminish with repeated applications due to factors such as insect resistance and life cycle dynamics. This study highlights the need for integrated pest management strategies that consider both chemical and biological control methods to manage aphid populations effectively.